Marital Philosophy and Home Value among the Annang of Nigeria: An Exploration of Selected Proverbs - Anana, Mariam (NIU Journal of Humanities; Vol. 8 Núm. 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023DO - 10.58709/niujhu.v8i4.1860, 2023)
Marital philosophies and home values are essential components of all living and progressive societies. They are potentiality used to create an enabling, sustainable and conducive environment and otherwise depending on their constituents and how they are applied on day-to-day interactions. A society devoid of the right marital philosophies may tend towards adopting negative home values that may ruin families, homes and the society at large. There are various factors that are responsible for one’s choices of ideal marital philosophies and home values for sustainable family life and the society.  This study therefore examines marital philosophies and home values encapsulated in the linguistically rich Annang proverbs from Akwa-Ibom, Nigeria. MAK Halliday’s Systemic Functional Grammar (and specifically the interpersonal metafunction) is adopted as our theoretical framework for the data analysis. Data were randomly selected from current Annang proverbs used in daily communicative purposes. This work adopts a qualitative (exploratory) research design; eleven (11) proverbs were randomly selected, presented and analysed.  We posit that proverbs are capsules of knowledge that marital philosophies and family values are enveloped. They can, and actually do serve as regulators of behaviours and moral templates upon which marital philosophes and home values are built.  With the data of proverbs drawn from Annang cultures and their corresponding English translations, we attempt to demonstrate the relevance of these cultural-linguistic tools in the reformation of character, value re-orientation and social redemption of man and his environment. Keywords: Cultural linguistic tools, Corresponding English translation, marital philosophies, home values, interpersonal functions